"I no longer count in German." On dominance shift in returnee heritage speakers. (12th September 2022) - Flores, Cristina; Zhou, Chao; Eira, Carina
Abstract: This study analyzes the degree of language balance in three groups of bilingual speakers of Portuguese and German: a group of Portuguese heritage speakers (HSs) living in Germany, another who returned to Portugal, and Portuguese late learners of German L2. Based on the DIALANG vocabulary size placement test, applied in German and in Portuguese, and on extralinguistic variables extracted from a background questionnaire, the results confirm high degrees of unbalanced language dominance favoring the societal language (SL) in HSs without the experience of return, and a leveling of language dominance in returnees. Language balance in returnees is the consequence of some loss of proficiency in the former SL (German) and reactivation of the heritage language (Portuguese). Current relative amount of contact with the two languages is correlated with language dominance only in the HSs and the late L2 speaker groups, whereas age of return and length of residence in Portugal explain language dominance in returnees. Self-reported proficiency is also predictive of language dominance and may be taken as complementary indicator.